2018
DOI: 10.1111/acps.12970
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol and childhood trauma predict psychological therapy response in depression and anxiety disorders

Abstract: Young AH, Cleare AJ. Hair cortisol and childhood trauma predict psychological therapy response in depression and anxiety disorders.Objective: Around 30-50% of patients with depression and anxiety disorders fail to respond to standard psychological therapy. Given that cortisol affects cognition, patients with altered hypothalamic-pituitaryadrenal (HPA) axis functioning may benefit less from such treatments. To investigate this, reliable pretreatment cortisol measures are needed. Method: N = 89 outpatients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
6
16
3
Order By: Relevance
“…The current null findings with regard to the cortisol and cortisone awakening response are in line with meta-analytical data suggesting no effect of salivary cortisol as a predictor for treatment response ( Fischer and Cleare, 2017 ). Despite the advantage of hair steroid analysis as an index of long-term integrated GCs, no predictive relationship was revealed, which is in contrast to one previous study on outpatients suffering from depression and anxiety disorders (e.g., PTSD, panic disorder, agoraphobia; Fischer et al, 2018 ). Again, the fact that the current study mainly focused on healthy spider-fearful individuals might have resulted in reduced variance in baseline long-term GC levels impeding the detection of meaningful relationships.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current null findings with regard to the cortisol and cortisone awakening response are in line with meta-analytical data suggesting no effect of salivary cortisol as a predictor for treatment response ( Fischer and Cleare, 2017 ). Despite the advantage of hair steroid analysis as an index of long-term integrated GCs, no predictive relationship was revealed, which is in contrast to one previous study on outpatients suffering from depression and anxiety disorders (e.g., PTSD, panic disorder, agoraphobia; Fischer et al, 2018 ). Again, the fact that the current study mainly focused on healthy spider-fearful individuals might have resulted in reduced variance in baseline long-term GC levels impeding the detection of meaningful relationships.…”
Section: Discussioncontrasting
confidence: 99%
“…An important advancement in this respect is hair steroid analysis, which represents a marker of long-term GC secretion integrated over periods of several months (Stalder et al, 2017). In fact, a recent study in this context observed higher hair cortisol concentrations as a predictor of improved therapy response in depression and anxiety disorder patients (Fischer et al, 2018). Hence, hair GC analysis may effectively complement research into endocrine predictors of clinical symptom change in response to exposure therapy.…”
Section: Introductionmentioning
confidence: 99%
“…To measure the psychopathology of depressive mood (using the patient health questionnaire-9 (PHQ-9)) 4749 , anxiety (by applying the generalised anxiety disorder 7-item (GAD-7)) 5052 , substance abuse (alcohol; using the CAGE questionnaire) 53–55 , cognitive style of daily living (by applying the adult attention-deficit/hyperactivity disorder (ADHD) self-report scale (ASRS-v.1.1)) 4446 , as well as social interaction patterns [of non-confrontational coping, including the anxiety-fear-avoidance for social situation 5659 (the Liebowitz social anxiety scale (LSAS)) and preference for non-face-to-face social interaction combined with smartphone overuse 60–62 (the smartphone addiction scale (SAS))], that have been associated with perceived verbal abuse (by applying the verbal abuse questionnaire (VAQ)), we applied several self-reporting questionnaire listed below.…”
Section: Methodsmentioning
confidence: 99%
“…This interaction could be key for understanding the etiological mechanisms involved in such conditions, as well as for identifying potential therapeutic mechanisms. [20][21][22][23][24][25][26] In addition, hair cortisol reflecting long-term HPA activity has recently emerged as a potential predictor of treatment response in anxiety and depression. 19 The therapeutic options available for chronic pain management are very extensive.…”
Section: Introductionmentioning
confidence: 99%